2013
DOI: 10.3109/0142159x.2012.746452
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional clinical training improves self-efficacy of health care students

Abstract: The study showed that interprofessional training improved students' perception of self-efficacy more than traditional clinical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 30 publications
2
45
1
2
Order By: Relevance
“…Despite this heterogeneity, we found evidence that students of mental health responded well to IPE, especially in terms of more positive attitudes toward the contribution of other professions [1,7,13,14,17,25] and increased knowledge of and skills in collaboration [1,7,13,14,17,26]. However, we found no substantial evidence of changes in behavior or organizational practices, which possibly reflects the complexity of IPE interventions and attitudinal differences toward IPE stemming from differences in work culture, as has also been found by other review studies [3,[28][29][30].…”
Section: Discussionsupporting
confidence: 56%
“…Despite this heterogeneity, we found evidence that students of mental health responded well to IPE, especially in terms of more positive attitudes toward the contribution of other professions [1,7,13,14,17,25] and increased knowledge of and skills in collaboration [1,7,13,14,17,26]. However, we found no substantial evidence of changes in behavior or organizational practices, which possibly reflects the complexity of IPE interventions and attitudinal differences toward IPE stemming from differences in work culture, as has also been found by other review studies [3,[28][29][30].…”
Section: Discussionsupporting
confidence: 56%
“…Interprofessional training that promotes a synthesised expertise of multiple healthcare professionals has been shown to improve self-efficacy and positive changes in practice (e.g. Nørgaard et al, 2013;Roush & Tyson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses were found to be more effective when they changed their behavior or conversation to meet the needs of parents. Norgaard et al [16] found that parents believed that doctors did an excellent job in providing them with information about their sick children. The latter study [16] also reported that nurses spent the most time with parents, explained their child's condition to them and were their principal source of information.…”
Section: Discussionmentioning
confidence: 99%
“…Norgaard et al [16] found that parents believed that doctors did an excellent job in providing them with information about their sick children. The latter study [16] also reported that nurses spent the most time with parents, explained their child's condition to them and were their principal source of information. Thus, it appears that who presents information -doctors or nurses -might not be important.…”
Section: Discussionmentioning
confidence: 99%